Product development : a structured approach to consumer product development, design, and manufacture - Mital, Anil (Elsevier/Butterworth-Heinemann, 2008)
Design and manufacture of new products has always been a team effort; but lately the team has been expanding. No longer can companies afford to keep the product design team working in isolation from the production and manufacturing team, not to mention the financial and accounting team For today's product development team has to comprise an integrated group of professionals working from the very beginning of new product planning on through design creation and design review and then on to manufacturing planning and cost accounting. Even when a product is conceived and goes into preliminary.
Keywords: New products -- Management.; New products -- Marketing.; Strategic planning.; elektronické knihy; electronic books